Uji Infeksi Cylindrocladium sp pada Tiga Klon Hibrid Eucalyptus grandis x eucalyptus pellita - Ervan F. Hutajulu; Nelly Anna; Edy Batara Mulya Siregar (Program studi Kehutanan USU, 2015)
One of the diseases that attack in the Eucalyptus nursery is Cylindrocladium causing Cylindrocladium foliar spots and foliar blight disease. Cylindrocladium found in eucalyptus nurseries PT Toba Pulp Lestari . According Sembiring (2008) research, Cylindrocladium fungal virulence is the highest of the pathogen found in nurseries . This study aimed to characterize the symptoms of foliar diseases caused by Cylindrocladium on the derived crosses hybrid clones of the type of Eucalyptus, Eucalyptus grandis x Eucalyptus pellita and measure the level of the intensity of the attack, the extent of the attack, as well as the reaction of plants (resistance) of the hybrid clones of Eucalyptus grandis x E. pellita. Infection is done by spraying inoculants fungi on leaves of three clones seedling of E. grandis x E. pellita age of two months, Clone IND 32, Clone IND 33 and Clone IND 45. The symptoms of infection that appearon leaves then reisolated by the method of Koch's postulates. Symptoms caused by infection Cylindrocladium on E. grandis x E. pellita leaves is blight disease. Symptoms begin with yellowish brown spots and will be widened (necrotic) then continue in severe leaf tissue death. The incubation period for infection of Cylindrocladium faster seen in clone IND 45, but the pace of progress has been slow. In clone IND 32 and IND 33 the incubation period of infection longer appear, but the pace of progress are most intense. Cylindrocladium infection does not affect the growth (resistance) of E. grandis x E. pellita seed age of two months. Key Words: Eucalyptus sp, Cylindrocladium sp, Infection Test, Leave Blight Disease